Hearing loss in skull fractures. - Momose, K J; Davis, K R; Rhea, J T (American Journal of Neuroradiology, 1983)
One hundred three cases of skull fractures in or around the temporal bone were reviewed for hearing loss. Of these, 100 patients had skull series, 66 had computed tomographic head scans, and 44 had polytomographic studies of the temporal bone. Hearing loss in head trauma can be grouped into four categories: conductive hearing loss, peripheral sensorineural hearing loss, central sensorineural hearing loss, and combinations of these hearing losses. The cause of conductive hearing loss and peripheral sensorineural hearing loss was usually identified by the type of temporal bone fracture. However, the cause of the central sensorineural hearing loss was more difficult to correlate with the brain lesions shown in the computed tomographic scans.